PC based passive infrared detector for the determination of human presence / Ahmad Latfi Salim - Salim, Ahmad Latfi (1994)
This report describes how computers based passive infrared detectors can be developed to determine the presence of human beings. This report contains 10 sections, covering pyroelectric detectors, signal conditioning; conversion between analog and digital signals, interfacing to the PC, results and discussions. Sections 1, introduces the needs for automation in the detection of the presence of human beings in the security sector. Section 2 and 3, covers the introduction to infrared radiation and the means of detecting and the various materials suitable for those purposes. Section 4, give a brief introduction on the infrared sensing on human beings. It also describes the pyroelectric detectors and materials used for the detection. Section 5, introduces the general proposed detection system, and describes briefly how the information from the physical world is converted to a form suitable for computer processing. Section 6, explain the design considerations and the circuit employed. Each circuit employed in the detection system and its operation is accordingly. The algorithm for interfacing the sensor to the computer is also describes.